Study of safety and efficacy of injection ferric carboxymaltose in iron deficiency anemia in pregnancy - Jain, Amrita; Asrani, Sonia S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Iron deficiency is a common nutritional deficiency amongst women of childbearing age. Peri-partum iron deficiency anemia (IDA) is associated with significant maternal, fetal and infant morbidity. Ferric carboxymaltose (FCM) may be better tolerated than the conventional blood transfusions and oral iron supplements. The study was designed to assess the safety and efficacy of IDA correction with intravenous (I.V.) FCM in pregnant women with mild, moderate and severe anemia in their second and third trimesters and their post-partum period. Methods: Prospective observational study; Treatment effectiveness was assessed by repeat hemoglobin (Hb) measurements and patient report of well-being in the postpartum period. Safety was assessed by analysis of adverse drug reactions and fetal heart rate monitoring during the infusion. Results: Intravenous FCM infusion significantly increased Hb values above baseline levels in all women. Fetal heart rate monitoring did not indicate a drug related negative impact on the fetus. No serious adverse effects were found Conclusions: Our prospective data is consistent with existing observational reports of the safe and effective use of ferric carboxymaltose in the treatment of iron deficiency anemia in peri-partum period.